2018
DOI: 10.1016/j.actamat.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effect of porosity on the polarisation-field response of ferroelectric materials

Abstract: This paper combines experimental and modelling studies to provide a detailed examination of the influence of porosity volume fraction and morphology on the polarisation-electric field response of ferroelectric materials.The broadening of the electric field distribution and a decrease in the electric field experienced by the ferroelectric ceramic medium due to the presence of low-permittivity pores is examined and its implications on the shape of the hysteresis loop, remnant polarisation and coercive field is d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 45 publications
(135 reference statements)
7
67
0
Order By: Relevance
“…Furthermore, pores could orient in a similar fashion as particles, thus changing the anisotropy of the properties. Zhang et al showed that the reduction of the remanent polarization with increasing porosity is lower in case of pores aligned to the applied electric field, [ 56 ] indicating that the effect on the piezoelectric charge coefficient is lower for aligned pores. Thus, pores seem to be the major contributor of the BT50 samples, which is even more apparent when compared with the BT52 samples.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, pores could orient in a similar fashion as particles, thus changing the anisotropy of the properties. Zhang et al showed that the reduction of the remanent polarization with increasing porosity is lower in case of pores aligned to the applied electric field, [ 56 ] indicating that the effect on the piezoelectric charge coefficient is lower for aligned pores. Thus, pores seem to be the major contributor of the BT50 samples, which is even more apparent when compared with the BT52 samples.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained (d 33 ) eff value for dense thin films is comparable to the values previously reported for dense BiFeO 3 thin films prepared by soft chemical deposition. 26,33 Recently, Zhang et al 34 reported experimental and modelling studies on the effect of the macro porosity volume fraction and morphology on the polarisation-electric field response of ferroelectric bulk materials. The results of the authors corroborate the results described here as they observed that porosity up to 25% volume leads to a decrease in coercive field with increasing porosity, and this was justified by the increase of compliance of the ceramic matrix which facilitates non-1801 domain switching.…”
Section: Resultsmentioning
confidence: 99%
“…However, the relationship between coercive field and porosity is not trivial and often nonlinear, as it can be influenced by the level of porosity and its distribution in the film. 31,32 PZT films pyrolyzed at the highest temperature (475 1C) display a remanent polarization of 23.7 mC cm À2 . Fig.…”
Section: Electromechanical Characterizationmentioning
confidence: 99%